Seasonal cycles in baseline mixing ratios of a large number of trace gases at the Mace Head, Ireland atmospheric research station. (15th July 2020) - Derwent, RichardG.; Parrish, DavidD.; Simmonds, Peter G.; O'Doherty, Simon J.; Spain, T. Gerard
Abstract: A flexible approach for quantifying average long-term changes and seasonal cycles has been applied to the baseline mixing ratios of thirty-two trace gases monitored at the Atmospheric Research Station located at Mace Head, Ireland on the Atlantic Ocean coastline of Europe. Almost all these trace gases exhibit minima in their baseline seasonal cycles during a two-month period from mid-July to the end of September and maxima during a six-month period between November and May. Relative seasonal cycle amplitudes are largest for those trace gases with the shortest atmospheric lifetimes and smallest for the longest. Robust relationships were found between the timings of the seasonal maxima and minima and their relative amplitudes with the atmospheric lifetimes of the trace gases. These relationships provide a basis for understanding the reasons that the seasonal cycles of a few species (that is, H2, CCl4 and the longest-lived gases) deviate significantly; they also have excellent potential as tools to assess global chemistry-transport model performance. Highlights: All trace gases studied exhibited summer minima and winter-spring maxima. Seasonal cycle minima move later in the year with increasing atmospheric lifetime. Relative amplitudes are largest for trace gases with shortest atmospheric lifetimes.